ANALISIS KEKUATAN IMPAK PADA MATERIAL KOMPOSIT BERPENGUAT LIMBAH FILTER ROKOK SEBAGAI BAHAN DASAR PEMBUATAN CANGKANG HELM - Diah Mayleni; Boy Rollastin; Masdani Masdani (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
Cigarette filter waste is one of the wastes that is difficult to recycle and has no selling value, so cigarette filter waste is used as an alternative material for making helmet shells. This study aims to determine how a composite material (ie 16% HGM, 76.5% epoxy, 7.5% cigarette filter waste) is used as a basic material in the manufacture of helmet shells. The testing process carried out is the charpy impact test with different specimen thicknesses (3 mm, 4 mm, 5 mm). Based on this study with a thickness of 3 mm, the highest average impact strength compared to other thickness specimens was 0.02868 J/mm2, at 4 mm thickness was 0.01628 J/mm2, at 5 mm thickness was 0.01025 J/mm2 .. In this test, compared with the results of the SNI helmet impact strength test of 0.00972 J/mm2 then all specimens passed the material test for SNI helmets.